Simultaneous Traumatic Avulsion of Flexor Digitorum Superficialis and Flexor Digitorum Profundus Tendons in Left Little Finger - Mohamed Maklad; Emily West; Sherif Wilson (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Avulsion injuries of the flexor digitorum profundus (FDP) tendon are common and widely reported [1-3]. Closed traumatic avulsion of the flexor digitorum superficialis (FDS) tendon is, however, rare, with few reported series of isolated FDS ruptures [3-6]. The FDS tendon is normally absent in the little finger of 33% of the population. There is a single case report documenting closed FDS and FDP injuries in the little finger. However, in this case the FDP ruptured at the DIPJ level, rather than being avulsed from its insertion [7]. We present a case of traumatic simultaneous avulsion of FDS and FDP tendons in the same finger.